Interactive effects of water stress, container size and fertilizer on survival, gas exchange and morphological traits of Quillaja saponaria seedlings - Espinoza, Sergio E; Santelices, Rómulo E; Cabrera, Antonio M; Magni, Carlos R (BOSQUE, 2017)
Quillaja saponaria is a valuable commercial and ecological Chilean native species that has suffered considerably degradation countrywide; however, the determination of the optimum characteristics of the planting stock, an important aspect in restoration projects, has receive little attention. The aim of this study was to evaluate the effect of container size and dose of fertilizer on morphological and physiological responses of Q. saponaria seedlings cultivated in a nursery under well-watered and water restricted conditions. After 27 days growing under contrasting watering regimes, growth, biomass allocation, and gas exchange were measured in 6-month-old seedlings. We found that survival, height and diameter increment, and root dry weight were higher in the wáter stressed seedlings cultivated in large containers. The water stressed seedlings cultivated in large containers also had superior stomatal conductance, however when the fertilizer dose was decreased, this trait decreased considerably. Thus, a superior performance in a water-restricted environment could be expected in those seedlings cultivated in larger containers with low fertilizer.